MEMBANGUN BISNIS BERKELANJUTAN BERBASIS KOMUNITAS (KAJIAN SOLUSI BISNIS MENYONGSONG ERA WEB 3.0) - Sunarso; Rochmad Fadjar Darmanto; Estuti Fitri Hartini; Karno (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Building a sustainable business requires strategic studies related to environmental changes and uncertain business ecosystems. The purpose of writing this paper is to examine and provide solutions in implementing web 3 technology in businesses that develop thanks to communities or groups of people who are members of autonomous organizations. The method used in this study is to carry out a series of stages covering the proposal of a business idea to test the web 3.0-based information technology platform namely solar, inter-stellar and LOBSTR with a network of stellar experts to create community tokens. The results of the study show that web 3.0 technology is very feasible to implement to support sustainable business continuity. Web 3.0 is decentralized and supports the creation of tokens based on blockchain technology that is user-friendly and protects sensitive user data with an easy private key, with a transaction speed of 10 seconds, easily implemented by the communitybased business world, especially in protecting individual user data. The conclusions and implications of the results of this study are that web 3 can be adopted in community-based business practices